Real-world effectiveness of antipsychotic treatment in psychosis prevention in a 3-year cohort of 517 individuals at clinical high risk from the SHARP (ShangHai At Risk for Psychosis). (July 2020) - Zhang, TianHong; Xu, LiHua; Tang, XiaoChen; Wei, YanYan; Hu, Qiang; Hu, YeGang; Cui, HuiRu; Tang, YingYing; Hui, Li; Li, ChunBo; Cao, LiPing; Lu, Zheng; et al.
Objective: Antipsychotics are widely used for treating psychosis, but it is unclear whether they can also prevent psychosis. This study attempted a longitudinal evaluation of antipsychotics under real-world conditions in China to evaluate their effect on the rate of conversion to psychosis in individuals with a clinical high risk (CHR) of psychosis. Method: A total of 517 CHR individuals were recruited between 2011 and 2016 and followed up for 3 years. Among these, 450 (87.0%) individuals completed follow-up, 108 (24.0%) showed conversion to psychosis and 309 (68.7%) received antipsychotics. The main outcome was conversion to psychosis. The sample was further stratified according to the severity of positive symptoms. Results: Patients who did not receive antipsychotics showed a lower conversion rate than those who did (17.7% vs 26.9%; odds ratio [OR] = 0.660, 95% confidence interval [CI] = [0.442, 0.985], p = 0.035). In mild CHR cases, antipsychotic treatment was more likely to be associated with conversion to psychosis, compared with the no-antipsychotics group, with no such difference observed in severe CHR cases. Among those who received antipsychotics, monotherapy or low-dose treatment was associated with lower conversion rates. Our results did not favor any specific type of antipsychotics and suggested that a very small subgroup of CHR individuals with severe positive and general symptoms but mild negative symptoms may benefit from antipsychotic treatment. Conclusions: Administration of antipsychotics to CHR patients is potentially harmful with no preventive benefits. We do not recommend antipsychotic treatment for CHR individuals, which is practiced widely in China, and strongly advise caution if these drugs are used.